Effect of sarpogrelate, a selective 5-HT2A receptor antagonist, on characteristics of coronary artery disease in patients with type 2 diabetes. (February 2017) - Lee, Dong-Hwa; Chun, Eun Ju; Hur, Jee Hye; Min, Se Hee; Lee, Jie-Eun; Oh, Tae Jung; Kim, Kyoung Min; Jang, Hak Chul; Han, Seung Jin; Kang, Doo Kyoung; Kim, Hae Jin; Lim, Soo
Abstract: Background and aims: Sarpogrelate, a 5-hydroxytryptamine type 2A antagonist, is a potential antiplatelet agent. We performed a randomized study to evaluate the effect of sarpogrelate on vascular health in Korean patients with diabetes. Methods: Forty diabetic patients aged 58.6 ± 6.8 years with 10–75% coronary artery stenosis, as assessed by coronary computed tomography angiography, were randomly assigned to sarpogrelate 300 mg/day plus aspirin 100 mg/day (SPG + ASA group) or aspirin 100 mg/day alone (ASA group) for 6 months. The primary endpoint of this study was the change in coronary artery disease including the calcium score (CACS), maximal stenosis, and plaque volume (calcified vs. noncalcified). The secondary endpoints were changes in biochemical parameters related to glucose and lipid metabolism, and in subclinical atherosclerosis assessed by ankle–brachial index and pulse wave velocity. Results: After 6-month treatment, there was no significant difference in the changes in CACS, coronary stenosis, ankle–brachial index, and pulse wave velocity, between groups. The total plaque volume decreased from 82.4 ± 14.5 mm 3 to 74.6 ± 14.4 mm 3 in the SPG + ASA group, but increased from 64.9 ± 16.0 mm 3 to 68.6 ± 16.3 mm 3 in the ASA group ( p < 0.05), mainly driven by changes in the noncalcified component (SPG + ASA group 15.6 ± 4.6 mm 3 to 11.2 ± 3.7 mm 3 vs . ASA group 21.2 ± 6.2 mm 3 to 22.8 ± 6.6 mm 3, p < 0.01). Serum C-reactive protein levels and homeostasis model assessment of insulin resistance tended to decrease in the SPG + ASA group, but they were not altered in the ASA group. Conclusions: The present study demonstrated that sarpogrelate treatment may decrease coronary artery plaque volume, particularly the noncalcified portion, in patients with diabetes. Highlights: Sarpogrelate, a selective 5-HT2A receptor antagonist, reduced coronary artery plaque volume significantly in patients with type 2 diabetes. Regression of atheroma was more prominent in noncalcified plaque than in calcified plaque. These beneficial effects are attributable to the pleiotropic properties including its anti-inflammatory and insulin-sensitizing properties.